Respuesta :

Answer: .36

Step-by-step explanation: If you follow PEMDAS the first step you would do is multiply 4 x 9 which gives you 36. Next, you subtract 36.36 - 36 which gives you your final answer of .36

[tex]\longrightarrow{\green{0.36}}[/tex] 

[tex]\large\mathfrak{{\pmb{\underline{\red{Step-by-step\:explanation}}{\red{:}}}}}[/tex]

[tex]36.36 - 4x[/tex]

Substituting [tex]x[/tex] = 9 in the above expression, we have

[tex]=36.36 - 4 \times 9 \\ \\ = 36.36 - 36 \\ \\ = 0.36[/tex]

Note:-

[tex]\sf\red{PEMDAS\: rule.}[/tex]

P = Parentheses

E = Exponents

M = Multiplication

D = Division

A = Addition

S = Subtraction

[tex]\large\mathfrak{{\pmb{\underline{\orange{Mystique35 }}{\orange{♡}}}}}[/tex]